Residents in Seattle, WA Report Differential Use of Free-Floating Bikeshare by Age, Gender, Race, and Location - Hirsch, Jana A.; Stewart, Ian; Ziegler, Sianna; Richter, Ben; Mooney, Stephen J. (Frontiers in Built Environment, 2019)
Bikesharing may have numerous urban health, sustainability, and mobility benefits. Bikesharing systems that do not require stations (i.e. “dockless,” or “free-floating” bikeshare) launched in North America in 2017. While this novel model may enhance access to and use of bikeshare by diverse populations, to date no work has examined equity in free-floating bikeshare use. This brief report uses a web-based panel survey (n=601) to provide sociodemographic characteristics of adult Seattle residents reporting bikeshare use during the first six months of a pilot free-floating program. One-third of Seattle adults surveyed reported trying free-floating bikeshare. These users were disproportionately young, male, White, resided closer to the city center, and already more likely to have or use a bicycle. Safety, social, spatial access, physical size, operation, technology, and cost barriers remained, particularly for males and non-White respondents. Almost half of non-users were open to trying free-floating bikeshare. However, these respondents hold limited potential to diversify the user population: while more likely to be female, like current riders, they were young and already using bicycles. If cities, researchers, and operators work together in the rapidly-shifting mobility landscape, they may be able to remove inequitably distributed barriers to transportation technology.